Interpersonal Meanings in Nike's “Winning Isn’t for Everyone” Instagram Campaign - Ilma Alfi Rahmi; Zulprianto Zulprianto; Eva Najma; Zulfakhri Dt. Majo Datuk (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2026)
This study examines how mood structure in Nike’s Winning Isn’t for Everyone campaign constructs interpersonal meaning between the brand and its audience. Drawing on Systemic Functional Linguistics (SFL) as proposed by Halliday and Matthiessen (2014), the study employs a qualitative descriptive approach. The data consist of 72 clauses derived from 53 Instagram captions posted on Nike’s official account under the hashtag #WinningIsntForEveryone. The captions were selected through clause segmentation, focusing on the primary caption content while excluding tagging elements. The findings reveal that declarative clauses are dominant (70.9%), followed by imperative clauses (27.7%), with interrogative clauses occurring minimally (1.4%). In terms of polarity, positive clauses account for 90.3% of the data, whereas negative clauses represent 9.7%. These patterns indicate that the campaign primarily relies on declarative mood and positive polarity to construct an encouraging and engaging interpersonal relationship with its audience.